(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: (1) To describe the quality of life (QoL) of patients with chronic kidney disease (CKD) undergoing maintenance hemodialysis and (2) to identify factors associated with their palliative care needs. Methods: A cross-sectional study was conducted on 72 patients with end-stage renal disease (ESRD) undergoing periodic hemodialysis at Thuy Nguyen Medical Center. Data were collected using the VietPOS and EQ-5D-5L instruments. Results: Regarding QoL, the most significantly affected domain was pain/discomfort (69.4%), followed by anxiety/depression (48.6%) and mobility (47.2%). The mean EQ-VAS score was 62.3 ± 14.8. Factors significantly associated with higher palliative care needs included low income (p=0.031), smaller household size (p=0.048), high ECOG performance status (p=0.004), and low hemoglobin levels (p=0.022). Conclusion: Patient quality of life is substantially impaired, primarily by pain and discomfort. Palliative care needs are strongly influenced by economic factors, family support, and performance and anemia status.